Use of the microbiome in the management of children with type 2 diabetes mellitus. Issue 4 (August 2019) - Brar, Preneet Cheema; Kohn, Brenda
Abstract : Purpose of review: The purpose of this review is to present recent data that defines our current understanding of the role of the gut microbiome in the development of T2DM. Recent findings: Recent studies focus on the physiology and molecular pathways of the gut microbiome–host interaction. Short-chain fatty acids (SCFAs) derived from the fermentation of plant-based nonsoluble fiber bind to G-protein-coupled receptors (GPR) GPR 41 and GPR 43 to induce enteroendocrine molecules that control appetite, and to upregulate intestinal gluconeogenesis gene expression that controls glucose regulation. "Metabolic endotexemia" reflects a state of low-grade systemic inflammation that results from lipopolysaccharide (LPS) release from the gut into the systemic circulation in response to a high-fat diet. Inflammatory pathways induced by LPS, activation of toll-like receptor-4 (TLR-4), and other inflammatory signaling pathways are mediators of systemic inflammation, insulin resistance and type II diabetes mellitus. Summary: Recent scientific data support that derangements in the composition of the microbiota, termed "microbiome dysbiosis" is a factor in the development of "metabolic endotoxemia" and T2DM. Therapeutic options that target the gut microbiome in the treatment of T2DM are explored.